21st Century Skills In The Teaching Of Foreign Languages At Primary And Secondary Schools - Cruz, Mário (2017)
Taking an experiential communicative approach (Fernández-Corbacho, 2014) into account, enriched by gamifi-cation strategies (Foncubierta & Rodríguez, 2015), in this paper we intend to disseminate teaching practices in English and Spanish as Foreign Languages at primary/secondary schools, which account for the development of 21st Century Skills, namely: collaboration and communication, creativity and innovation, critical thinking and problem solving. Therefore, we will present practices, developed within a Master’s Degree practical training, which illustrate the work of these skills in the classroom using: a) Web 2.0 applications in collaborative learning; b) creative and (hyper)sensory tasks which develop critical reflection; c) cross-cultural activities.